Development and testing of the ACT-1 experimental facility for hypersonic combustion research. (7th March 2016) - Baccarella, D; Liu, Q; Passaro, A; Lee, T; Do, H
Abstract: A new pulsed-arc-heated hypersonic wind tunnel facility, designated as ACT-1 (Arc-heated Combustion Test-rig 1), has been developed and built at the University of Notre Dame in collaboration with the University of Illinois at Urbana-Champaign and Alta S.p.A. The aim of the design is to provide a suitable test platform for experimental studies on supersonic and hypersonic turbulent combustion phenomena. ACT-1 is composed of a high temperature gas-generator system and a model scramjet combustor that is installed in an open-type vacuum test section of the wind tunnel facility. The gas-generator is designed to produce high-enthalpy (stagnation temperature  =  2000 K–3500 K) hypersonic flows for a run time up to 1 s. The supersonic combustor section is composed of a compression ramp (scramjet inlet), an internal flow channel of constant cross-section, a fuel jet nozzle, and a flame holder (wall cavity). The facility allows three-way optical accesses (top and sides) into the supersonic combustor to enable various advanced optical and laser diagnostics. In particular, planar laser Rayleigh scattering (PLRS), high-speed schlieren imaging and OH-planar laser induced fluorescence (OH-PLIF) have successfully been implemented to visualize the turbulent flows and flame structures at high speed flight conditions.